Variasi Penggunaan Kata Sapaan Bahasa Minangkabau dalam Novel Mak Adang dari Nagari Keramat karya Andi Mulya - Azahra, Siti Fatimah; Liusti, Siti Ainim (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to provide a comprehensive description of the variations in the usage of Minangkabau greetings in the novel Mak Adang dari Nagari Keramat by Andi Mulya. The variations in greeting usage encompass both kinship and non-kinship greetings. Kinship greetings encompass greetings that are based on relationships within the nuclear family as well as the extended family. On the other hand, non-kinship greetings consist of greetings that are based on customary, religious, and general situations. This research adopts a qualitative approach and utilizes descriptive methods. The data used in this study consist of the greeting words uttered by the speakers and their conversation partners in the novel Mak Adang dari Nagari Keramat by Andi Mulya. The data sources are the sentences in the novel that contain Minangakabau greeting words. The data collection process employed a listen and read method, along with recording techniques. Data validation was achieved through triangulation techniques. The research data were analyzed through the following stages: (1) data inventory stage; (2) data classification stage; (3) data description stage. The findings of this study are as follows: (1) there are 21 forms and usages of kinship greeting words, which consist of 10 forms of kinship greetings based on the nuclear family and 11 forms of kinship greetings based on the extended family. (2) There are 35 forms and usages of non-kinship greeting words, which consist of three forms of non-kinship greetings based on religious greetings, six forms of non-kinship greetings based on customary greetings, and 26 forms of non-kinship greetings based on general greetings.